Studies on suitability to incorporate Piper betel leave extract in flavored milk - Patange, Dnyaneshwar D.; Gore, R. B.; Patil, Y. N.; Gaikawad, N. B.; Kalyankar, S. D.; Khedkar, C D (Indian Journal of Dairy Science, 2024)
The present study was carried out to investigate the antioxidant and phenolic potential of Piper betel leaves (PBL)-fortified flavored milk (FM) and thereby assess its storage stability. The FM was prepared by fortifying it with aqueous extract of PBL, sugar, and CMC stabilizer @ 5.15, 10.30, and 0.1 %, respectively followed by its pasteurization (FM1). The bottles were stored at 5±1ºC and compared with control (FM2) i.e. milk without PBL extract. Each sample was evaluated at an interval of 4 days for changes, if any in the sensory attributes, proximate composition, physicochemical properties, antioxidant and phenolic potential, and microbial quality till its sensorial acceptance. It was observed that the sample FM2 recorded flavor score 7.00 for flavor. It was further seen that the storage period, treatment, and their interaction effect had significant bearing (P